Blood is blood [large type] - Thomas, Will, 1958- (Thomas, Will, 1958- Barker & Llewelyn novel, 2019)
"In 19th century London, a bombing injures private enquiry agent Cyrus Barker, leaving it up to his soon-to-be-married junior partner Thomas Llewelyn to find the person trying to murder them both before it's too late"--